The Impact of Visual Cartoons on Student Learning Outcomes in Science Education - Acesta, Arrofa (Indonesian Journal of Elementary Teachers Education, 2024)
ABSTRACTThe issue addressed in this study pertains to the substandard academic performance of students at SD Negeri 2 Mekarwangi, Lebakwangi Subdistrict, as evidenced by a 74% failure rate to meet the Minimum Criteria for Mastery (KKM). The research aims to explore the impact of employing visual media cartoons on student learning outcomes in the subject of Changing Earth and Sky Appearances for fourth-grade students. The study employs a quasi-experimental design, dividing students into experimental and control groups (IV A and IV B, totaling 30 students each) to assess the efficacy of visual media cartoons. Data is collected through pre and post-tests consisting of 20 multiple-choice questions. Analysis methods include tests for data normality, homogeneity, hypothesis, and N-Gain. The pre-test averages were 50.17 and 51.67 for the experimental and control groups, respectively. Post-test averages were notably higher for the experimental group (78.17) compared to the control group (66.83), indicating a positive influence of visual media cartoons on student learning outcomes. Statistical analysis confirmed the significance of this influence (t-value = 5.70 > t-critical = 2.00), thereby supporting the alternative hypothesis (Ha). In summary, the study provides evidence that the integration of visual media cartoons enhances science learning outcomes for fourth-grade students at SD Negeri 2 Mekarwangi, Lebakwangi District, Kuningan Regency.Keywords: Visual Media Cartoons, Student Learning Outcomes.Science Education